Determinants of Tree Growing and Cover Retention in Arid and Semi-Arid Areas of East Africa: The Case of Machakos County, Kenya - Heeran M. Mutuku; Harun M. Kiruki (European Scientific Journal, ESJ, 2023)
Rapid human population growth, increased demand for land, over-exploitation and the degradation of local natural resources have led to serious socio-economic and environmental challenges in Machakos County, Kenya, East Africa. This has led to a drastic reduction in tree cover in arid and semi-arid areas over the years. To reverse this trend, it is important to understand the socio-economic factors that determine household tree growth and cover retention in Machakos County. Based on a structured questionnaire targeting 412 respondents (233 men and 179 women) as well as 2 focus group discussions and 14 key informants, we assessed the determinants of tree growing and cover retention among small scale farmer households using a logistic regression model. The study found that socioeconomic variables that significantly influenced tree growing and cover retention in Machakos County in Kenya included gender (p= 0.011), household size (p=0.030), Farm size (p= 0.005), and title deed ownership (p=0.023). The respondents used tree products to enhance their socio-economic resilience. In total, 58 different types of tree species were planted or retained on the farms. The major tree species included Eucalyptus saligna, Grevillea robusta, Mangifera indica, Persea americana, Croton megalocarpus, and Terminalia brownie. Based on our findings we recommend more involvement of women and youth in tree-growing activities in the Matungulu Sub-county.